(untitled) (Boletin Médico de Postgrado, 2020)
The main historical events in the study and fight against polio are shown, its isolation by Karl Landsteiner in 1909, the development of the first vaccine with dead virus (Jonas Salk, 1955), the second vaccine with live attenuated virus (Albert Sabin, 1961) and the gradual reduction of polio worldwide, reaching less than 200 cases a year (wild virus).